RESPONSE ANALYSIS OF SHEARER BEVELING FEEDING PROCESS POWER - MAO Jun; XIE ChunXue; XIE Miao; LIU ZhiXiang (Jixie qiangdu)
The oblique condition of study on mining machine drum load characteristics is the drum（ pick） squeeze coal judgment conditions,using the squeeze area and the coal and rock fracture theory,oblique roller axial additional load are obtained. Accurately understand the oblique cutting and feeding roller load changes,to avoid the proportion of the existing calculation method and power calculation method of defects and errors,for shearer initiative designed to provide theoretical basis.Using numerical simulation software MATLAB draw before and after coal mining machine oblique cutting and feeding roller force,and uses Adams multi-body dynamics simulation software response simulation of shearer beveling feeding coal mining process mobility. The vibration displacement and acceleration of each mass block are obtained under different traction speeds. It provides a theoretical basis for the stability,reliability design and dynamic analysis of the whole machine and its components,and it has a certain guiding role for the active design of the shearer.